pendidikan islam The method of Islamic education during Demak kingdom - Muhammad Ilyas (Al-Hayat Al-Istiqomah Foundation, 2020)
In the concept of Islamic education, there are several kinds ofideas that have been listed in an education. In Islam, it does not forget a history where the teachings derived from the knowledge come. Especially in the land of Java, there has been a long Demak kingdom has stood and proved by its historical relics. Whit the concept of Islamic education, no other Demak kingdom must have its idea of Islamic education in the upbringing ofIslamic in his time. This research was conducted quantitatively, the type of literature research. It will explore the literature related to Islamic education during the Demak kingdom by using the research model for the study of Islam history at the time of the Demak Kingdom, The aim of this study to see the model ofeducation that applied at that time can develop Islam rapidly which still no communication like today. Research of result is the method that used during the time of Demak kingdom was the lecture method, inserts, demonstrations and experiments and observational research using a cultural approach.